(untitled) (Journal of Research Updates in Polymer Science, 2015)
The morphology evolution of hydroxyl zinc monomethacrylate (HZMMA) in hydrogenated nitrile rubber (HNBR) during its formation, and effect of synergistic behavior of HZMMA and carbon black (CB) in HNBR on its properties, were investigated. Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), transmission electron microscopy (TEM) and X-ray diffraction (XRD) were used to probe the reaction of in-situ polymerized HZMMA. The results showed that an ionic polymer interpenetrating HNBR, due to homo-polymerization or graft polymerization of HZMMA solid monomer occurred, and poly-HZMMA particles, confirmed by FTIR and TEM, were formed during the HNBR vulcanization process. This kind of morphology for the HNBR composites played a very significant role in the HNBR reinforcement. At ambient temperature, the mechanical properties of HNBR composite filled with pure PHZMMA was much superior to those of the HNBR/PHZMMA/CB composites; however, when the temperature was increased to above 50°C, the decrease of the tensile strength for the latter was slower, and the tensile strength was always higher than that of the HNBR composites reinforced with pure PHZMMA at the same temperature. The elongation at break above 80°C was also always higher than that of the HNBR/PHZMMA sample. The HNBR/PHZMMA/CB composites showed excellent air oven aging resistance.